2016
DOI: 10.1007/s00264-016-3280-6
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient mortality after elective primary total hip and knee joint arthroplasty in Botswana

Abstract: The inpatient mortality rate of 0.86 % following TJA is higher than the reported rates in the developed countries but comparable with data from other developing countries. The inpatient mortality rate following TKA was higher than that following THA and cardiovascular events proved to be the main cause of death. We recommend formal cardiology assessment and close peri-operative monitoring of all patients with a history of cardiovascular disease undergoing TJA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…It is possible that the statistically significant increased risk of 90day mortality associated with <4 weeks of prophylactic treatment may be due to arterial thrombosis or cardiac-related mortality [16], or premature cessation of therapy not documented in the examined studies. The most common cause of death after TJA is not VTE, but cardiovascular complications for both hip arthroplasty [84e86] and knee arthroplasty [86]. Blom et al [87] also found ischemic heart disease and cerebrovascular events contributing more to mortality after hip fracture than PE.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the statistically significant increased risk of 90day mortality associated with <4 weeks of prophylactic treatment may be due to arterial thrombosis or cardiac-related mortality [16], or premature cessation of therapy not documented in the examined studies. The most common cause of death after TJA is not VTE, but cardiovascular complications for both hip arthroplasty [84e86] and knee arthroplasty [86]. Blom et al [87] also found ischemic heart disease and cerebrovascular events contributing more to mortality after hip fracture than PE.…”
Section: Discussionmentioning
confidence: 99%
“…Where papers were identified to duplicate reporting of earlier work, they were included with explanations provided. 5,1012 The final search was undertaken on 4 November 2018. The preferred reporting items for systematic reviews and meta-analyses (PRISMA) process was followed (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Total hip and knee joint replacement ranks among the most successful surgical interventions and several developing countries in Africa have started to perform these procedures that are routine in developed countries [ 1 ]. Both total hip replacement (THR) and total knee replacement (TKR) have been demonstrated to provide long-lasting pain relief and substantial and sustained improvement in joint functioning and health-related quality of life [ 2 ].…”
Section: Introductionmentioning
confidence: 99%